Cells of the Innate and Adaptive Immune Systems in Kaposi’s Sarcoma - Owen Ngalamika; Sody Munsaka (Journal of Immunology Research)
Kaposi’s sarcoma (KS) is an angioproliferative malignancy whose associated etiologic agent is the Kaposi’s sarcoma-associated herpesvirus (KSHV). KS is the most prevalent malignancy among HIV-infected individuals globally and is considered an AIDS-defining malignancy. The different forms of KS including HIV-associated KS, iatrogenic (immunosuppression-related) KS, and classical KS in elderly males suggest that immune cell dysregulation is among the key components in promoting KS development in KSHV-infected individuals. It is therefore expected that different cell types of the immune system likely play distinct roles in promoting or inhibiting KS development. This narrative review is focused on discussing cells of the innate and adaptive immune systems in KSHV infection and KS pathogenesis, including how these cells can be useful in the control of KSHV infection and treatment of KS.